2020
DOI: 10.4049/jimmunol.1801430
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Localize in Hypoxic Zones of Tumors and Secrete CCL-2 under Hypoxia through Activation of L-Type Calcium Channels

Abstract: Hypoxia is a condition that together with low pH, high amounts of reactive oxygen species (ROS), and increased adenosine levels characterize tumor microenvironment. Mast cells (MCs) are part of tumor microenvironment, but the effect of hypoxia on the production of MC-derived cytokines has not been fully described. Using the hypoxia marker pimonidazole in vivo, we found that MCs were largely located in the low-oxygen areas within B16-F1 mice melanoma tumors. In vitro, hypoxia promoted ROS production, a ROS-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…We cannot exclude the possibility that a percentage of LDMs or HDMs are tumor-associated macrophages [ 19 , 84 ]. There is also the possibility that in vivo exposure to altered tumor microenvironment, such as low pH [ 85 ], hypoxia [ 86 , 87 ], lactate [ 88 ] or adenosine [ 89 ] may have affected the phenotypic and the functional activity of lung macrophages. In addition, it has been recently demonstrated that macrophages isolated from lung adenocarcinoma differ phenotypically from those obtained from distant and macroscopically normal lung parenchyma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that a percentage of LDMs or HDMs are tumor-associated macrophages [ 19 , 84 ]. There is also the possibility that in vivo exposure to altered tumor microenvironment, such as low pH [ 85 ], hypoxia [ 86 , 87 ], lactate [ 88 ] or adenosine [ 89 ] may have affected the phenotypic and the functional activity of lung macrophages. In addition, it has been recently demonstrated that macrophages isolated from lung adenocarcinoma differ phenotypically from those obtained from distant and macroscopically normal lung parenchyma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic environments are highly immunosuppressive due in part to low pH and elevated concentrations of ROS, adenosine, and nitric oxide [ 143 ]. Interestingly, mast cells are frequently localized in hypoxic regions of tissues such as melanoma and associated with the active angiogenic processes initiated in these microenvironments [ 5 , 144 ].…”
Section: Environmental and Physiological Pathways That Differentially Program Mast Cellsmentioning
confidence: 99%
“…A moderate level of hypoxia does not induce significant cell death of bone marrow-derived mast cells, nor does it inhibit their degranulation [ 144 ]. Instead, hypoxic conditions drive HIF1α and subsequent ROS production in exposed mast cells as seen in vitro studies [ 144 ].…”
Section: Environmental and Physiological Pathways That Differentially Program Mast Cellsmentioning
confidence: 99%
See 2 more Smart Citations